Assessment of absolute coronary flow and microvascular resistance reserve in patients with severe aortic stenosis. (3rd October 2022) - Gallinoro, E; Paolisso, P; Vanderheyden, M; Esposito, G; Bertolone, D T; Mileva, N; Bermpeis, K; Belmonte, M; De Colle, C; Candreva, A; Penicka, M; Collet, C; et al.
Abstract: Introduction: The development of left ventricular hypertrophy in patients with severe aortic stenosis (AS) is accompanied by adaptive coronary flow regulation, both in epicardial and microvascular compartment, which ultimately lead to a chronic ischemic insult even in the absence of obstructive coronary artery disease. Intracoronary continuous thermodilution of saline through a dedicated infusion catheter is a novel tool that allows to measure absolute coronary flow and microvascular resistance at rest and during hyperemia and to calculate both coronary flow reserve (CFR) and Microvascular Resistance Reserve (MRR) Purpose: We aimed to assess absolute coronary flow, microvascular resistance, CFR and MRR in patients with AS, by continuous intracoronary thermodilution, comparing these hemodynamic findings with a propensity-score matched contemporary cohort of patients without AS. Methods: Absolute coronary blood flow and microvascular resistance were measured by continuous thermodilution in 29 patients with AS and compared to 15 controls matched for age, gender, diabetes mellitus and functional severity of epicardial coronary lesions. Myocardial work, total myocardial mass and LAD-specific mass were quantified by echocardiography and cardiac-CT. Results: Patients with AS presented a significantly positive LV remodeling with lower global longitudinal strain and higher global work index compared to controls (p<0.02). Total LV myocardial mass and LAD-specific myocardial mass were significantly higher in patients with AS. Compared to matched controls, absolute resting flow in the LAD was significantly higher in the AS cohort (86 [66–107] ml/min vs 68 [52–75] ml/min, p=0.036), resulting, in lower CFR (2.30±0.69 vs 2.89±0.77, p=0.005) and MRR (2.73±0.74 vs 3.53±0.95, p=0.005) in the AS cohort compared to controls (Figure 1). No differences were found in hyperemic flow and resting and hyperemic resistances. Interestingly, hyperemic myocardial perfusion (calculated as the ratio between the absolute coronary flow in the LAD and the mass subtended by the vessel, expressed in mL/min/g), but not resting, was significantly lower in the AS group (1.9 [1.5–2.5] ml/min/g vs 2.3 [2–3.1] ml/min/g p=0.036). Conclusions: In patients with severe aortic stenosis and non-obstructive coronary artery disease, with the progression of LVH, the compensatory mechanism of increased resting flow maintains an adequate perfusion at rest, but not during hyperemia (Figure 2). As consequence, both CFR and MRR are significantly impaired. Funding Acknowledgement: Type of funding sources: None.